Penerapan Model Simulasi Antrian Single-Phase Multi-Channel untuk Optimasi Layanan Coffeeshop Presensia di Kota Medan - Efani Desi; Siti Aliyah; Fitri Pranita Nasution; Enni Maisaroh; Indah Lestari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study applies an M/M/s single-phase multi-channel queue simulation model (Poisson arrivals λ avg. 19 cust/hr, exponential service μ=6 cust/hr/barista, FIFO) via POM-QM for Windows to optimize Coffeeshop Presensia services in Medan (observation Nov 1-30, 2024, 3-9 PM). Baseline (s=4: 2 baristas + 2 cashiers) shows Lq=3, Wq=0.15 hr (9 min), Po=0.02 on busy days. Optimal scenario (3 baristas + 2 cashiers) reduces Wq to ~2 min (95% CI: 1.8-2.2 min), ρ =0.67. Recommendation: add 1 barista during peaks. This adjustment resulted in a significant reduction in the average customer waiting time, from 9 minutes to around 2 minutes, ensuring that the service provided meets the standard time expected by customers. This study provides valuable insights into improving service efficiency through more strategic resource allocation at Coffeeshop Presensia.